Accuracy of aortic dissection detection risk score alone or with D-dimer: A systematic review and meta-analysis. Issue 3 (1st October 2020) - Tsutsumi, Yusuke; Tsujimoto, Yasushi; Takahashi, Sei; Tsuchiya, Asuka; Fukuma, Shingo; Yamamoto, Yosuke; Fukuhara, Shunichi
Abstract : Background: To evaluate the diagnostic accuracy and clinical utility of the acute aortic dissection detection risk score (ADD-RS) alone or with D-dimer as a screening test to exclude acute aortic syndrome. Methods: We conducted a systematic review and meta-analysis of studies examining the diagnostic accuracy of ADD-RS. We searched MEDLINE, Embase and Cochrane Controlled Register of Trials up to 12 December 2018. Results: We identified nine studies involving 26, 598 patients for ADD-RS alone and 3421 patients with D-dimer. Overall, the methodological quality based on the Quality Assessment of Diagnostic Accuracy Studies 2 was moderate to high. Bivariate meta-analyses showed that the pooled sensitivities were 0.94 (95% confidence interval (CI) 0.90, 0.96) at the threshold of ADD-RS ≥1, 0.46 (95% CI, 0.34, 0.59) at ADD-RS ≥2, 1.00 (95% CI 0.99, 1.00) at ADD-RS ≥1 with D-dimer and 0.99 (95% CI 0.97, 1.00) at ADD-RS ≥2 with D-dimer. For the low prevalence population, failure rate and efficiency were 0.8% and 38.3% at ADD-RS ≥1, 0.03% and 14.5% at ADD-RS ≥1 with D-dimer, and 0.1% and 33.6% at ADD-RS ≥2 with D-dimer, respectively. For the high prevalence population, failure rate and efficiency were 3.8% and 33.3% at ADD-RS ≥1, 0.2% and 12.3% at ADD-RS ≥1 with D-dimer and 0.6% and 28.4% at ADD-RS ≥2 with D-dimer, respectively. Conclusions: ADD-RS alone or with D-dimer was a useful screening test with high sensitivity to exclude acute aortic syndrome. However, the optimal threshold of ADD-RS alone or with D-dimer may depend on the clinical setting.